A comparative study of numerical approaches for the computation of effective properties of micro‐heterogeneous materials. Issue 1 (25th January 2021) - Assaf, Rama; Scheunemann, Lisa; Birk, Carolin; Schröder, Jörg; Ooi, Ean Tat
Abstract: The paper presents a comparative study of the finite element method (FEM) and the scaled boundary finite element method (SBFEM) for the numerical evaluation of the volume‐averaged stress of composites. Two‐dimensional meso‐scale models of concrete represented by digital images and discretized using an automatic mesh generation algorithm are considered. The different computational approaches are discussed and compared with respect to accuracy and efficiency for both scenarios.